2013
DOI: 10.1016/j.apmr.2013.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Using the Timed Up & Go Test in a Clinical Setting to Predict Falling in Parkinson's Disease

Abstract: Objective To investigate the ability of the Timed Up & Go test to identify patients with Parkinson's disease at risk for a fall. Design Cross-sectional cohort study. Setting Sixteen participating National Parkinson's Foundation Centers of Excellence. Participants A query yielded a total of 2985 records (1828 men and 1157 women). From these, 884 were excluded because of a lack of crucial information (age, diagnosis, presence of deep brain stimulation, disease duration, inability of performing the Timed Up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
96
1
9

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(107 citation statements)
references
References 17 publications
(18 reference statements)
1
96
1
9
Order By: Relevance
“…Their results indicated that, overall, 74% of their sample could be correctly classified, but classification of fallers (sensitivityϭ54%) was lower compared with classification of nonfallers (specificityϭ85%). 8 Our literature search did not result in a previous study investigating discriminant ability of a BM test.…”
Section: Discriminant Ability and Sddmentioning
confidence: 96%
See 1 more Smart Citation
“…Their results indicated that, overall, 74% of their sample could be correctly classified, but classification of fallers (sensitivityϭ54%) was lower compared with classification of nonfallers (specificityϭ85%). 8 Our literature search did not result in a previous study investigating discriminant ability of a BM test.…”
Section: Discriminant Ability and Sddmentioning
confidence: 96%
“…Their results indicated that 74% of the participants with PD were correctly classified as "fallers" or "nonfallers" based on their TUG time, and they reported a cutoff score of 11.5 seconds for discrimination between those who did and did not fall. 8 Bed mobility (ie, turning, sitting, and then standing up from the bed) also has been investigated in people with PD. A 3-point ordinal rating scale method showed acceptable interrater and intrarater reliability (Cohen kappaϭ.64 -.79).…”
mentioning
confidence: 99%
“…Unlike the SPPB, the TUG test has no ceiling effect and owing to simplicity, validity, and high reliability, its use has become widespread in health care and across different disease states and general, older populations. [12][13][14][15][16] A few studies have investigated the TUG test in patients with COPD, although, to date, these have been generally in small populations and often not with comparator groups. 6 , 8 , 17-19 Where there has been a control group, the TUG test time was increased in patients.…”
mentioning
confidence: 99%
“…4 Finally, the Timed Up and Go test could be given to assess falling risk. 5 Author Response: Yuichiro Shirota, Masashi Hamada, Tokyo; Yoshikazu Ugawa, Fukushima, Japan: Ramos et al raised a number of interesting points regarding our study. The primary endpoint of our study was the change in UPDRS part III from the baseline.…”
mentioning
confidence: 99%